P 30 Voxel-based intensometry of high resolution T1 MRI predicts disease progression in ALS. Issue 10 (October 2017) - Hartung, V.; Batyrbekova, M.; Stubendorff, B.; Ringer, T.; Prell, T.; Mayer, T.E.; Witte, O.W.; Grosskreutz, J.
Abstract : Background: ALS is known to be a fatal and yet heterogenous neurodegenerative disease. Despite the constantly improvement in diagnostic tools there is still a massive demand for reliable prognostic biomarkers. In particular, disease load and disease aggressiveness in the brain is hard to quantify. Recently, we have developed voxel-based intensitometry (VBI) as derivative of voxel-based morphometry (VBM) which detected the extent and severity of ALS in high resolution T1 in a cohort of 33 patients (Hartung et al., 2014 ). Objectives: We aimed to assess the power of VBI in a larger cohort in identifying subgroups of patients and predicting disease progression in ALS. To this end we correlated VBI results with real clinical parameters and a novel clinical marker of disease progression (D50) which represents a 50% decay in ALSFRS-R on an individually fitted sigmoidal curve per patient. Methods: 101 ALS patients from the neurologic outpatient department of the Jena University Hospital were enrolled to the study and underwent clinical and imaging studies containing T1-weighted non-contrast enhanced MRI. Imaging datasets were offline computed using Voxel-based intensometry (1). The novel disease progression marker D50 was calculated modeling the course of ALSFRS-R. Correlation analysis of D50 and VBI was done to find regions of significant correlation. Results: The mean age of the patients was 60.7 ( ± 11.6) years. The patient group included 29 bulbar and 72 limb onsets. Average disease duration was 26 months and mean ALSFRS-R was 38.7. Mean progression rate (deltaALSFRS-R) was 0.67 and the mean D50 was 47 months. There was a significant correlation of the clinical disease progression marker D50 and VBI in the subcentral white matter of the precentral gyrus in its extremity and body sectors. Conclusion: D50 is a reliable clinical biomarker of disease progression; it facilitated finding subcortical white matter brain alterations directly correlated to overall ALS course. The combination of VBI and D50 allows to gain a perspective of disease progression at any given time point during ALS. While further unraveling of ALS heterogeneity, the combination of D50 and VBI may provide simple tools for stratification and monitoring in clinical trials. Acknowledgment: This research is supported by BMBF (Bundesministerium für Bildung and Forschung) in the framework of the E-RARE programme (PYRAMID) and JPND (OnWebDUALS and SOPHIA) of the European Union in collaboration with the Neuroimaging Society in ALS (NiSALS) MRI repository Jena.